2016
DOI: 10.1142/s0219455415500054
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of Railway Vehicles Running on Long-Span Cable-Stayed Bridge Under Uniform Seismic Excitations

Abstract: In order to evaluate the dynamic response of the train running on long-span cable-stayed bridges under uniform seismic excitations, a time-domain framework of analysis for the trainbridge system is established. The rail irregularities are treated as internal excitation and seismic loads as external excitation considering the inertia forces induced by the 3D seismic waves. The vehicles are modeled as mass-spring-damper systems, and the cable-stayed railway bridge is simulated by¯nite elements. A comprehensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Modeling of vehicle-bridge system: (a) mass-spring-damper model of vehicle (Li et al, 2005, 2016) and (b) bridge cross-section.…”
Section: Response Predictions Of Vertical Train-bridge Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling of vehicle-bridge system: (a) mass-spring-damper model of vehicle (Li et al, 2005, 2016) and (b) bridge cross-section.…”
Section: Response Predictions Of Vertical Train-bridge Systemsmentioning
confidence: 99%
“…The vehicle dynamic system can be modeled as a massspring-damper system (Li et al, 2005(Li et al, , 2016, as shown in Figure 8(a). The train model has two suspension systems consisting primarily of seven rigid bodies: one vehicle body, two bogies, and four wheelsets.…”
Section: Models Of Vehicle and Bridgementioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid worldwide development of high-speed railways, the use of long-span railway bridges in high-intensity seismic regions or strong wind regions is becoming increasingly common (Chen et al, 2019; Deng et al, 2020; Li et al, 2015b; Liang et al, 2019; Olmos and Astiz, 2018; Wang et al, 2014; Zhou and Chen, 2015). Such strong excitations can cause nonlinear bridge behaviors, including geometric nonlinearity (Apaydin et al, 2016), material nonlinearity (Yang et al, 2018), and boundary nonlinearity at the bearings (Borjigin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This model has been widely used among researchers due to its simplicity. [1][2][3][4][5][6][7] However, the accuracy of this model was recently challenged by some researchers. 8,9 Based on the results from a¯eld study, Yin et al 8 found that the single-point model may overestimate the dynamic ampli¯cation of the bridge responses, especially under distressed bridge deck conditions.…”
Section: Introductionmentioning
confidence: 99%